Effect of metformin, glibenclamide and insulin on lipid profile in type 2 diabetic patients - M. Merkhan, Marwan (Tikrit Journal of Pharmaceutical Sciences, 2023)
Objective: to investigate the differences between the effects of metformin, glibenclamide, a combination of metformin plus glibenclamide and insulin on glycemic control and lipid profile. Subjects and methods: this study was conducted in Mosul-Iraq. A total of 136 type 2 diabetic patients were enrolled in this study. Thirty two, apparently healthy volunteers, were also included in the study as a control group. Blood sample were taken from the patients and controls and the serum were analysed for measurement of fasting serum glucose (FSG), HbA1c and lipid parameters. Results: the FSG of the metformin group (8.78±3.55 mmol/l) was significantly lower than that of glibenclamide and insulin groups (11.45±2.79 mmol/l), (13.16±6.18 mmol/l) respectively and there were non significant differences between the total cholesterol (TC) (4.49±0.93 mmol/l), high density lipoprotein (HDL-c) (1.3±0.48 mmol/l), low density lipoprotein (LDL-c) (2.43±0.95 mmol/l) and atherogenic index (AI) (3.72±0.93) of metformin group in comparison to that of the control group (4.69±0.39 mmol/l), (1.34±0.38 mmol/l),( 2.80±0.62 mmol/l) and (3.82±1.21) respectively. The levels of TC (4.49±0.93 mmol/l), LDL-c (2.43±0.95 mmol/l) and the value of AI (3.72±0.93) for the metformin group were significantly lower than that of other studied groups, while the HDL-c of the metformin group (1.3±0.48 mmol/l) was significantly higher than that of other studied groups. The level of triglyceride (TG) of metformin and metformin plus glibenclamide groups (1.68±0.81 mmol/l), (1.85±0.76 mmol/l) respectively was significantly lower than that of the glibenclamide group (2.85±1.01 mmol/l). Conclusion: this study concluded that antihyperglycemic therapy with metformin in type 2 diabetic patients may have uniquely beneficial metabolic effects in addition to their glucose lowering effect. Key words: type 2 diabetes mellitus, lipid profile, metformin, glibenclamide, insulin